2011 Triennial Surveillance Review : Overview Paper. (Policy Papers; Policy Paper, 2011)
This paper assesses progress in strengthening Fund surveillance and identifies needed improvements. It differs from past reviews insofar as it: (A) encompasses not only bilateral but also multilateral surveillance; and (B) steps-up external inputs in the form of studies by outside observers, commentaries, and assessment of recommendations by an external advisory group.